An Overview of siRNA Delivery Strategies for Urological Cancers - Nadia Halib; Nicola Pavan; Carlo Trombetta; Barbara Dapas; Rossella Farra; Bruna Scaggiante; Mario Grassi; Gabriele Grassi (MDPI, 2024)
Indexed by WOS/SCOPUS/ERA